Debating your plate : the most controversial foods and ingredients - Minetor, Randi (Santa Barbara, California : Greenwood, 2022)
"This book examines the most controversial foods and ingredients, providing an objective, well-balanced look at the health benefits and risks of each. It equips readers with the information they need to make their own informed decisions about what they eat"--
Why is nutrition so controversial? -- The history of food controversies -- How to evaluate nutrition research and health claims -- Foods and ingredients: Artificial flavorings. Artificial food colors. Artificial sweeteners. Bottled water. Caffeine. Carbonated beverages. Carrageenan. Chocolate. Coconut oil. Cruciferous vegetables. Diary products. Eggs. Essential oils. Farm-raised fish and seafood. Fruit and vegetables juices. Genetically modified foods. Gluten. Grains. Grass-fed beef. Green tea. Guar gum. Olive oil. Organic foods. Phosphorus-containing food additives. Plant-based meats. Probiotics. Raw milk. Red meat. Salt. Saturated fat. Soy. Sugar alcohols. Superfoods. Vegetable oil. Wine. Xanthan gum.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 30, 2021).
eBooks on EBSCOhost
Keywords: Nutrition; Food preferences; Diet; Food habits; Ingestion; Nutritional Physiological Phenomena; Food Preferences; Feeding Behavior; Nutrition; Préférences alimentaires; Alimentation; Habitudes alimentaires; diet; Ingestion; Diet; Food habits; Food preferences; Nutrition